Business Development Strategy through Multi-Method Business Planning - Lucky Purnama; Keni Karnawati (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examines the strategic feasibility of reopening PT Mahaka Gemilang Mandiri’s branch in Cianjur, Indonesia, through an innovative business plan integrating localized credit restructuring, community trust, and digital innovation. Utilizing a qualitative case study design, data were triangulated from in-depth interviews, field observations, and financial records. The analytical framework synthesized SWOT, IFAS, and EFAS matrices with entrepreneurial models, including Design Thinking, the Business Model Canvas (BMC), and the Timmons Model. Findings reveal significant market opportunities in restructuring non-performing loans (NPLs) within the MSME and agrarian sectors. The proposed